Site-specific growth dynamics and yield patterns in Populus deltoides against edaphic variability over seven age-gradations. - Ashok Kumar Dhakad; Tarsem Singh; Avtar Singh; Kuldip Singh (PLoS ONE)
Most studies are focusing on general soil fertility effects on poplar growth rather than site-specific variations in edaphic factors considering the soil texture and profile as factors on poplar productivity and increments with age. Poplar (Populus deltoides Marsh.) grown in three different types of soil and across seven age-gradations were evaluated for growth behaviour and productivity pattern. We selected three nearby; even-aged poplar stands (PS1 with loamy sand, PS2 with silt loam, and PS3 with sandy loam texture) from poplar plantations, each with varying edaphic and similar agrometeorological conditions. We collected a composite soil sample for each transect at three distinct soil depths (0-30, 30-60, and 60-90 cm) and determined the physicochemical characteristics of the soil. Significant differences in soil texture and characteristics were noted across the three poplar stands (PS1, PS2 and PS3) due to variations in soil particle composition with depth. PS2 had more silt and clay with higher electrical conductivity (EC) and saturated hydraulic conductivity (SHC), while PS1 was richer in phosphorus, and PS3 had sandy textures and higher organic matter content. Early growth (height and diameter at breast height) was highest in PS3 but transitioned to PS2 after the fifth year. Leaf area, crown spread, timber weight, and total biomass also peaked in PS2 across age gradations. Current Annual Increment (CAI) values for tree growth variables increased initially but declined after the third age-gradation. For pulpwood, biomass productivity was 9.28% higher than that of PS2 and 29.15% higher than that of PS1, while PS2's productivity was 15.60% higher than that of PS3 and 45.81% higher than that of PS1 due to favorable texture and nutrient retention required for poplars. The study found the highest productivity (42.40 m³ha ⁻ ¹yr ⁻ ¹) in PS3 during a 5-year cycle, but PS2 excelled in subsequent years due to consistent nutrient availability. Thus, optimal growth was observed in soils with a balanced composition of sand (75-80%), silt (6-8%), and clay (13-17%). Soil organic carbon and phosphorus showed strong positive correlations with timber weight and growth parameters. The findings underscore the need for tailored management practices, including soil preparation before planting followed by precise fertigation to optimize the productivity of poplar plantations.